Zāhid aur do kahāniyāṉ - Žūliyāṉ (Sānjh, 2013)
Zāhid – ʿAdīl kā safar – Mengal Novelette on different themes
Novelette. - In arab. Schrift, Urdu. - Title on t.p. verso in roman: Zahid aur do khanian
Keywords: Urdu fiction